Case report: narcolepsy type 1 in an adolescent with HIV infection—coincidence or potential trigger?. Issue 30 (July 2018) - Scherrer, Karin Sofia; Relly, Christa; Hackenberg, Annette; Berger, Christoph; Paioni, Paolo
Abstract: Rationale: Despite the acknowledged importance of environmental risk factors in the etiology of narcolepsy, there is little research on this topic. HIV as a trigger for narcolepsy has not been systematically investigated. Patient concerns: We describe a case of narcolepsy type 1 (NT1) in an adolescent with HIV infection presenting with increased daytime sleepiness and excessive weight gain. Diagnoses: NT1 was diagnosed according to the criteria of the third edition of the International Classification of Sleep Disorders (ICSD-3). Interventions: Pharmacological treatment with methylphenidate. Outcomes: Four months after initiation of methylphenidate therapy the increased daytime sleepiness improved and excessive weight gain stopped. Lessons: Diagnosis of NT1 can be challenging at disease onset and is often delayed, especially in the pediatric population, because symptoms usually evolve gradually. The case presented here raises the possibility that the HIV infection may play a role in the pathogenesis of NT1 serving as trigger for autoimmune-mediated destruction of hypocretin-secreting neurons.